Carotenoid composite particles with low contact angle as well as raw material composition, preparation method and application of carotenoid composite particles

Through the low-temperature solid phase multiple co-grinding technology, the problems of high-temperature degradation and multi-phase switching in carotenoid microencapsulation are solved, and the stable embedding of carotenoid composite particles is achieved and the applicability of multiple applications is achieved.

CN119586773APending Publication Date: 2025-03-11INNOBIO CORP LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411915793.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The prior art requires high temperature melting when microencapsulating carotenoids, resulting in carotenoid degradation, and traditional methods involve multiphase switching and the use of organic solvents, affecting the environment and safety.

Method used

The low-temperature solid phase multi-co-grinding technology is used to reduce the contact angle of carotenoids, and solve the problem of complex system transformation of solid-phase-oil phase-water phase, and avoid the use of high temperature and organic solvents.

Benefits of technology

It has achieved stable embedding of carotenoids, good water solubility and high temperature stability, and is suitable for a variety of application scenarios, such as solid beverages, liquid beverages and tablets.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119586773A_ABST
    Figure CN119586773A_ABST
Patent Text Reader

Abstract

The invention discloses carotenoid composite particles with a low contact angle as well as a raw material composition, a preparation method and application of the carotenoid composite particles. According to the method, the problems that carotenoid is poor in water solubility and easy to degrade are solved, and the use risk of organic reagents is reduced. The composite particles contain 5-20% of carotenoid (such as lutein, beta-carotene and the like), a carrier, an emulsifier, a small molecule filler and an antioxidant. Through multiple times of low-temperature co-grinding, the contact angle is gradually reduced, and it is ensured that the particles have excellent hydrophilicity and stability. According to the process, the production process is simplified, the energy consumption is reduced, the stability of the product during rapid dissolution and dispersion in cold water and high-temperature sterilization is ensured, and the floating oil or layering phenomenon is avoided. And the final product is suitable for various foods and health-care product preparations such as solid beverages, liquid beverages, tablets and the like, as well as skin care products and cosmetic products, is particularly suitable for application scenes needing high-temperature treatment, and provides better stability and safety guarantee.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of microcapsule preparation, and in particular to a carotenoid composite particle with a low contact angle, a raw material composition, a preparation method and an application thereof. Background Art

[0002] Carotenoids are a general term for an important class of natural pigments, which are commonly found in yellow, orange-red or red pigments of animals, higher plants, fungi and algae.

[0003] Carotenoids belong to tetraterpene organic molecular pigments, which are isoprenoid polymers containing 40 carbons, that is, tetraterpene compounds. Typical carotenoids are formed by 8 isoprene units connected end to end. According to their structure, they can be divided into carotenes and xanthophylls. Carotenes include α-carotene, β-carotene, γ-carotene and lycopene, which are all polyene tetraterpenes containing 40 carbons, formed by isoprene connected head to tail or tail to tail. Luteins include lutein, lutein esters, zeaxanthin, etc., which contain oxygen-containing groups such as hydroxyl, epoxy, aldehyde, and ketone in their structures.

[0004] The structure of carotenoids gives them strong antioxidant capacity. In the body, they can protect the body's tissue cells by quenching singlet oxygen, scavenging free radicals and other antioxidant behaviors, thereby protecting the biological system from some potential harmful effects caused by excessive oxidation reactions. They can also be converted into vitamin A in the human body, which is essential for maintaining normal visual function, immune system and skin health.

[0005] However, due to its sensitivity to light, heat and oxygen, it is easy to degrade and lose its functionality; at the same time, its water-insoluble characteristics also bring many disadvantages to our absorption and utilization. Therefore, most of them are embedded by microencapsulation to improve their stability and water solubility.

[0006] The traditional microencapsulation method is to dissolve the crystalline carotenoids in oil, then raise it to a very high temperature to make it molten, emulsify the molten oil into the water phase to form an emulsion, and then dry it. For example, JP2020528746A discloses a method for preparing microcapsules of fat-soluble nutrients, dissolving carotenoids in oil, then raising the temperature until the oil phase is completely melted, requiring a high temperature of 100 to 200°C, mixing with the water phase and adding it to a multi-stage series cavitation emulsifier, continuously emulsifying under high pressure, and then spray drying.

[0007] Patent CN202010603864.8 discloses a method for extracting lutein esters and a method for preparing water-soluble lutein ester microcapsules. Lutein esters and zeaxanthin are both carotenoids. In this method, lutein esters are dissolved in vegetable oil and then melted at 70-135°C for 15-30 minutes. After adding the aqueous phase, the mixture is sheared, homogenized, and finally spray-dried to obtain a powder.

[0008] Similarly, patent CN202110882814 discloses a method for preparing carotenoids, wherein the oil phase is subjected to ultra-high temperature instantaneous melting (0-300°C), and the instantaneous melting time is within 5 seconds. It is then rapidly cooled to below 30°C.

[0009] Although the above patents solve the emulsification problem of carotenoids, they still inevitably use high temperatures. High-temperature melting will degrade and denature the temperature-sensitive carotenoids, greatly reducing their efficacy and increasing their degradation rate during the shelf life. Although instantaneous melting can reduce the melting time, the process conditions of heating to 300°C and then lowering to 30°C in a short period of time are too harsh and the requirements on the equipment are too high, which cannot be met by ordinary equipment.

[0010] Due to the adverse effects of content degradation caused by melting, people have improved the melting embedding method and used organic solvents instead of oils as carriers of carotenoids.

[0011] For example, CN200910222596.9 discloses a zeaxanthin micro-pill and a preparation method thereof, which comprises taking zeaxanthin, adding an excipient, crushing to a micronized level, and mixing; dissolving a binder in a solution of water, anhydrous ethanol or aqueous ethanol; and using micro-pill molding technology to form micro-pills. This method uses anhydrous ethanol, and the introduction of the solvent undoubtedly puts pressure on the environment, and the residual solvent also leaves hidden dangers to the safety during the administration process.

[0012] Patents US11197493B2, CN105077203A and CN101910526B also use a large amount of water-immiscible organic reagents (solubility in water <10%) such as methanol, ethanol, n-propanol, isopropanol, 1,2-butanediol 1-methyl ether (1-methoxybutan-2-ol), 1,2-propylene glycol 1-n-propyl ether (1-propoxypropan-2-ol), tetrahydrofuran or acetone in emulsification. Then, a desolventizing device is used to remove the solvent as much as possible.

[0013] Although the above patents avoid degradation caused by high temperature, they introduce organic reagents, which undoubtedly puts great pressure on the environment, waste liquid treatment and discharge. At the same time, the residual solvent also leaves hidden dangers to the safety during the use process.

[0014] Later, for the sake of environmental protection, people adopted the method of removing the solvent from the dry crystals and grinding the auxiliary materials in a water system to embed carotenoids. This method avoided high temperature and organic reagents.

[0015] For example, WO2017168006A1 discloses a beverage containing stable ground lutein particles, wherein the molar ratio of lutein to zeaxanthin is 9:1. After the modified starch, glucose syrup and sucrose are dissolved in water, lutein and zeaxanthin and any mixture of carotenoids are added to obtain a suspension, which is then ground and finally spray-dried to obtain particles. The entire process dissolves the auxiliary materials (solids) and carotenoids (solids) in the aqueous phase, then grinds them into a uniform emulsion and spray-dries them to obtain the product. The process is cumbersome, involves multi-phase switching, and has high production capacity.

[0016] Similarly, CN101873848B discloses a tabletable preparation of a lipophilic health ingredient, which requires four different temperature ranges, namely 20-50°C, 30-70°C, 45-65°C and 45-80°C, during the process of drying the emulsion into a powder, and the drying process is complicated.

[0017] Although the above patents solve the problems of melting and residual dissolution, the overall process is complex, involving the process from solid phase to water phase, and then drying the water phase back to solid. The overall industrialization has high energy consumption and difficulty. In summary, both the melting method and the solvent method also involve a complex process from solid phase to oil phase (organic phase), then emulsifying from oil phase (organic phase) to water phase, and then drying from water phase back to solid phase. At the same time, most of the above patents are only applicable to one or two market application directions for one dosage form. Therefore, a preparation process that has both low temperature and green environmental protection, as little phase change as possible in the process, and covers as many application fields as possible is an urgent problem that carotenoid products need to solve. Summary of the invention

[0018] In view of the deficiencies in the prior art, the present invention aims to provide a raw material composition of low contact angle carotenoid composite microparticles prepared only in the solid phase under low temperature conditions without multi-phase switching; it relates to a technology of multiple co-grinding of low temperature solid phase, which can make the reaction proceed in the positive direction by reducing the contact angle, solve the deficiencies of the complex system transformation of solid phase-oil phase-water phase-solid phase, the degradation and denaturation problems caused by high temperature melting, and the safety problems caused by the use of organic reagents in the preparation process of carotenoids; at the same time, this composition can be dissolved and dispersed in cold water, and the rehydrated solution can be sterilized at high temperature to maintain uniformity and stability without floating oil and wall hanging, and can also be used as an active substance for tableting, so as to achieve the effect of no flowery tablets and no dizzy tablets. It can be applied in various application scenarios such as solid beverages, liquid beverages, tablets, etc.

[0019] (1) The first aspect of the present invention provides a raw material composition of carotenoid composite particles, wherein the carotenoid content is 5-20%;

[0020] The carotenoids include but are not limited to lutein, zeaxanthin, fucoxanthin, lutein esters, β-carotene, lycopene, etc., and the total carotenoid content is 5-20wt%, preferably 5-15wt%, and most preferably 10-15wt%. The carotenoid content is defined as the total carotenoid content multiplied by the composition ratio of the specific carotenoid in the liquid phase.

[0021] Furthermore, the raw material composition of the carotenoid composite particles contains the following components, by weight:

[0022] Carotenoid crystals: 5-30 parts by weight, preferably 10-22 parts by weight; most preferably 10-15 parts by weight

[0023] Carrier: 10-40 parts by weight, preferably 20-30 parts by weight; most preferably 20-25 parts by weight

[0024] Emulsifier: 0-8 parts by weight, preferably 2-4 parts by weight; most preferably 2-3 parts by weight

[0025] Small molecule filling: 6-25 parts by weight, preferably 15-20 parts by weight; most preferably 15-20 parts by weight

[0026] Antioxidant: 1-5 parts by weight, preferably 0.01-1 parts by weight of fat-soluble antioxidants; most preferably 0.1-0.5 parts by weight, 2-4 parts by weight of water-soluble antioxidants; most preferably 2-3 parts by weight;

[0027] Furthermore, the carotenoid crystals have a total pigment content of 30-90wt% and a water content of <5%. The pretreatment method is as follows: fully mixing marigold extract and 3-5 times the amount of anhydrous ethanol solution, adjusting the pH, and then isomerizing and stirring at a high temperature of 100-120°C for at least 1-2h, and then neutralizing, filtering, washing, and drying to obtain the carotenoid crystals.

[0028] Raw material composition of carotenoid composite microparticles: This is a composition containing carotenoids and other auxiliary ingredients (such as carriers, emulsifiers, small molecule fillers, antioxidants, etc.). It can be made into solid dosage forms such as powders and granules.

[0029] Carotenoids: refers to specific carotenoid compounds, such as lutein, zeaxanthin, fucoxanthin, lutein esters, β-carotene, lycopene, etc.

[0030] Carotenoid crystals: refers to the crystalline form of carotenoids obtained by a specific pretreatment method. Further, the carrier is selected from at least one of modified starch, gum arabic, octenyl succinic acid monoarabic gum ester, gelatin, agar, sodium caseinate, and seaweed polysaccharide. Further preferred carriers are selected from at least one of modified starch, gum arabic, and octenyl succinic acid monoarabic gum ester.

[0031] Furthermore, the emulsifier is selected from: sucrose fatty acid esters with an HLB value of 3 to 18, polyglycerol fatty acid esters, mono- and di-glycerol fatty acid esters, diacetyl tartaric acid monoglyceride, phospholipids, Tween, tween, or mixtures thereof.

[0032] Further preferred emulsifiers are composed of emulsifiers having HLB values ​​of 3-8, 9-14 and 15-18 respectively.

[0033] More preferred emulsifiers are composed of emulsifiers having HLB values ​​of 3-6, 9-12 and 15-18 respectively.

[0034] The most preferred emulsifier is composed of emulsifiers with HLB values ​​of 3-6, 9-12 and 15-18, respectively, and the ratio is 1.5-2.5:0.8-1.2:1.5-2.5, and the most preferred ratio is 2:1:2.

[0035] Furthermore, the small molecule filler is selected from at least one of white sugar, glucose powder, maltooligosaccharide, solid corn syrup, isomaltooligosaccharide, fructooligosaccharide, resistant dextrin, lactose and xylitol.

[0036] Furthermore, the antioxidant is selected from at least one of mixed tocopherols, dlα-tocopherol, ascorbyl palmitate, BHT, ascorbic acid, sodium ascorbate, and tea polyphenols.

[0037] Furthermore, the fat-soluble antioxidant is selected from at least one of mixed tocopherols, dlα-tocopherol, ascorbyl palmitate, and BHT;

[0038] Furthermore, the water-soluble antioxidant is selected from at least one of sodium ascorbate, sodium ascorbate, and tea polyphenols.

[0039] The second aspect of the present invention provides a carotenoid composite particle, which is composed of carotenoid, a carrier, an emulsifier, a small molecule filler and an antioxidant; more preferably, the carotenoid composite particle is prepared using the composition described above; and has the following properties:

[0040] a) Contact angle ≤ 20°, showing excellent hydrophilicity;

[0041] More preferably, the composite microparticles also have property b) the particle size D90 after rehydration is ≤ 1.5 microns, ensuring good dispersibility and stability;

[0042] More preferably, the invention also has property c) the moisture content is ≤ 4%, ensuring stable storage in a low moisture environment;

[0043] More preferably, it also has property d) ash content ≤ 3% and high purity;

[0044] More preferably, it also has property e) a bulk density between 0.40 and 0.70 g / mL, ensuring appropriate fluidity and compaction performance;

[0045] More preferably, it also has property f) surface oil content ≤ 0.5%, low surface oil means high encapsulation efficiency and more stable composite particles;

[0046] More preferably, it also has property g) being completely soluble or dispersible in cold water to meet various application requirements;

[0047] More preferably, it also has property h) remaining stable under high temperature sterilization conditions without obvious precipitation or oil floating phenomenon.

[0048] The highly hydrophilic carotenoid composite microparticles of the present invention contain protected and modified carotenoids in their structure, which are surrounded by a layer of emulsifier. The emulsifier acts as a medium to achieve directional arrangement between the carotenoids and the carrier, with the polar groups facing the polar solid surface and the non-polar groups pointing to the medium, thereby enhancing the stability of the microparticles. In addition, the small molecule fillers fill the gaps on the surface of the carrier, further strengthening the integrity of the structure. The antioxidants are distributed at different positions of the microparticles according to their properties, ensuring the long-term stability of the product. This unique microstructure gives the microparticles excellent physical and chemical properties, such as high hydrophilicity, good dispersibility and thermal stability, making them suitable for use in a variety of food and pharmaceutical preparations, especially in liquid beverages, tablets and capsules.

[0049] (2) The third aspect of the present invention provides a method for preparing carotenoid composite particles, which is achieved by multiple co-grinding in a low-temperature solid phase, and the specific steps are as follows:

[0050] A) The pretreated carotenoid crystals, emulsifier and antioxidant are mixed uniformly and co-grinded at low temperature to obtain a co-grind 1.

[0051] B) The carrier, the emulsifier and the co-grinding product 1 are mixed uniformly, and co-grinded again at low temperature to obtain a co-grinding product 2.

[0052] C) The small molecule filler and the co-grinding material 2 are uniformly mixed, and after the third low-temperature co-grinding, the particles are sieved according to the required particle size to obtain the final carotenoid composite particles.

[0053] Further preferably, the low temperature solid phase is co-grinded multiple times:

[0054] A) The particle size of co-grind 1 is 10-600 μm and the contact angle is 60-90°.

[0055] B) The particle size of the co-grind 2 is 10-600 microns and the antenna angle is 20-60°.

[0056] C) The particle size of the co-grind 3 is 10-800 μm; the contact angle is 0-20°.

[0057] Further preferably, the low temperature solid phase is co-grinded multiple times:

[0058] A) The co-grinding temperature is -25 to 0°C.

[0059] B) The co-grinding temperature is 10-30°C.

[0060] C) The co-grinding temperature is 10-60°C.

[0061] Further preferably, other parameters and equipment of the low-temperature solid phase multiple co-grinding are:

[0062] A) The co-grinding time is 15-45 min.

[0063] B) The co-grinding time is 15-45 min.

[0064] C) The co-grinding time is 5-20 min.

[0065] Further preferably, the co-grinding equipment includes but is not limited to ultrafine grinder, low-temperature freezing grinder, planetary mill, impact grinder, air flow grinder, pulverizer and granulator.

[0066] Further preferably, the sieve has a mesh size of 20 to 200.

[0067] The fourth aspect of the present invention is to provide the application of the above-mentioned carotenoid composite particles in the food, health care products and cosmetics industries.

[0068] Further preferably, specific applications in the food industry include food additives and colorants.

[0069] Further preferably, the food additives and colorants are used in beverages, baked goods, margarine, candies and dairy products.

[0070] More preferably, specific applications in the health care product industry include nutritional supplements.

[0071] More preferably, the nutritional supplement is applied to flavored juices, solid beverages, liquid beverages, sports drinks, probiotic products, candies, tablets, capsules, eye drops, and eye wash solutions.

[0072] More preferably, specific applications in the cosmetics industry include skin care products and makeup products.

[0073] Further preferably, the skin care products and makeup products are applied to moisturizing cream, anti-wrinkle eye cream, sunscreen, isolation cream, essence, facial mask, eye patch, lipstick, and lip balm.

[0074] Further preferred is the use of the carotenoid composite microparticles of the present invention in the preparation of liquid beverages and tablets. When used in liquid beverages, the carotenoid composite microparticles show good stability and no precipitation or oil floating under high temperature sterilization conditions. When used in tablets, the carotenoid composite microparticles show good retention rate and no halo phenomenon under high humidity and high temperature conditions.

[0075] Compared with the prior art, the present invention has the following beneficial effects:

[0076] The present invention uses low-temperature solid-phase multiple grinding technology to modify carotenoids in sections to achieve a step-by-step reduction in the contact angle of carotenoids, thereby solving the problems of poor water solubility and self-instability of carotenoids, and obtaining carotenoid composite particles with good storage stability, high temperature stability and solubility in water.

[0077] At the same time, in terms of preparation technology, the shortcomings of the traditional process of solid-oil-water emulsification and then drying back to the solid phase in the complex system transformation and the degradation and denaturation problems caused by high-temperature melting have been optimized; the preparation of carotenoid composite particles is carried out entirely in the solid phase, which simplifies the cumbersome process, reduces production energy consumption, and optimizes the cost of industrialization; similarly, the low temperature throughout the process ensures the stability of the properties and content of carotenoids.

[0078] The resulting carotenoid composite particles or their compositions can be widely used in functional foods. Due to their low contact angle characteristics, they can meet the application requirements of solid direct-drinking beverages, liquid functional beverages, health care oral liquids, tablets, capsules, etc. It is particularly emphasized that their high-temperature sterilization performance in liquid beverages is particularly excellent, and they can achieve stable content, uniform appearance, no floating oil, and no stratification during the 90-120°C sterilization process. BRIEF DESCRIPTION OF THE DRAWINGS

[0079] Figure 1-1 The solution state of lutein composite microparticles A prepared by the melting method in liquid beverage applications after sterilization at 90°C for 30 minutes. The figure shows that the solution is light orange-yellow, and a dark yellow oil ring appears on the top of the solution, proving that the lutein composite microparticles A prepared by the melting method are easy to demulsify and bleach oil under high temperature conditions.

[0080] Figure 1-2 The solution state of lutein composite microparticles B prepared by wet grinding method in liquid beverage application after sterilization at 90℃ for 30min. The figure shows that the solution is light orange-yellow, the solution is clearly stratified, and there is obvious precipitation at the bottom, which proves that lutein composite microparticles B prepared by wet grinding method are prone to phase separation under high temperature conditions, affecting the uniformity of the solution.

[0081] Figure 1-3 The solution state of lutein composite microparticles C prepared by low-temperature solid phase multiple co-grinding method in liquid beverage application after sterilization at 90℃ for 30min. The figure shows that the solution is orange-yellow, and there is no dark red oil ring or stratification in the solution. The solution state is uniform and good, which proves that the lutein composite microparticles prepared by low-temperature solid phase multiple co-grinding method are stable under high temperature conditions and have no floating oil and stratification.

[0082] Figure 2-1 The solution state of lutein ester composite microparticles in liquid beverage applications with an addition order of HLB values ​​of 3-6, 9-12 and 15-18 and a ratio of 2:1:2 after sterilization at 120°C. The figure shows that the solution is orange-yellow and the solution is uniform without precipitation, proving that the lutein ester composite microparticles prepared according to the conditions described in this article with the HLB value of the emulsifier, the addition order and the ratio of the emulsifier can keep the solution uniform and stable under the sterilization condition of 120°C.

[0083] Figure 2-2 The solution state of lutein ester composite microparticles in liquid beverage applications after sterilization at 120°C with an addition order of HLB values ​​of 3-6, 9-12 and 15-18 but a ratio other than 2:1:2. The figure shows that the solution is orange-yellow and there is a small amount of fine precipitation at the bottom of the solution, proving that the emulsifier HLB value and addition order are as described herein, but the ratio is not as described herein, and the emulsification system of the lutein ester composite microparticles prepared under sterilization conditions at 120°C is destroyed, and the uniformity and stability of the solution cannot be maintained.

[0084] Figure 2-3 The solution state of lutein ester composite microparticles in liquid beverage applications after sterilization at 120°C with an HLB value of 15-18, 3-6 and 9-12 in the order of addition and a ratio of 2:1:2. The figure shows that the solution is orange-yellow and there are large pieces of precipitation at the bottom of the solution, proving that the emulsifier HLB value and the order of addition are not as described in this article, but the lutein ester composite microparticles prepared in the ratio described in this article have their emulsification system destroyed under the sterilization condition of 120°C, and cannot maintain the uniformity and stability of the solution.

[0085] Figure 2-4After sterilization at 120°C, the HLB values ​​are 3-6, 9-12 and 15-18 and the ratio is 2:1:2, but the co-grinding material 1 is not added with an emulsifier. The solution is orange-yellow and there are a large number of fine particles at the bottom of the solution, which proves that the emulsification system of the lutein ester composite microparticles prepared with the HLB value and ratio of the emulsifier as described in this article, but the addition order is not as described in this article, is severely damaged and cannot maintain the uniformity and stability of the solution.

[0086] Figure 3-1 This is a scanning electron microscope image of carotenoid composite particles 1. The image shows that the particles are of different sizes and have a relatively smooth and round surface.

[0087] Figure 3-2 This is a scanning electron microscope image of carotenoid composite particles-2. The image shows that the particle surface is rough and irregularly round.

[0088] Figure 3-3 This is a scanning electron microscope image of carotenoid composite microparticles-3. The image shows that the surface of the microparticles is relatively smooth and irregularly round.

[0089] Figure 4-1 The XRD diagram of carotenoid composite particles-1 shows the diffraction peak at 2θ angle, which proves that carotenoid composite particles-1 have no lattice structure.

[0090] Figure 4-2 The XRD diagram of carotenoid composite microparticles-2 shows the diffraction peak at 2θ angle, which proves that carotenoid composite microparticles-2 have no lattice structure.

[0091] Figure 4-3 The XRD diagram of carotenoid composite microparticles-3 shows a diffraction peak at an angle of 2θ, which proves that carotenoid composite microparticles-3 have no lattice structure. DETAILED DESCRIPTION

[0092] The present invention is further described below in conjunction with examples, but it should be understood that the protection scope of the present invention is not limited to the following examples and the process parameter ranges in the examples.

[0093] In the present invention, unless otherwise specified, percentages and percentage contents are all by mass. Unless otherwise specified, the experimental methods used are all conventional methods, and the materials and reagents used can be purchased from commercial sources.

[0094] The present invention adopts the following methods to measure and evaluate the products.

[0095] The contact angle measurement method of the present invention is as follows: the present invention adopts a contact angle measuring instrument, using distilled water as the medium (1g / cm 3) was measured. The carotenoid composite microparticles were first made into flat sheets using a tablet press, placed on a sample platform, and measured using the sessile drop method, that is, distilled water was placed on the pressed flat tablet by an injection unit, and the image of the drop was captured by a high-resolution camera, and then the static contact angle was automatically calculated by the software.

[0096] Example 1 Effect of low temperature solid phase multiple co-grinding method on the contact angle of carotenoid composite particles

[0097] Formulation 1 (dry mixing): 10 g of zeaxanthin crystals, 10 g of modified starch, 3.2 g of mono- and diglycerol fatty acid esters (HLB value 3-6), 1.6 g of polyglycerol fatty acid esters (HLB 9-12), 3.2 g of sucrose fatty acid esters (HLB 15-18), 25 g of maltodextrin and 4 g of sodium ascorbate are directly mixed and mixed using a mixer to obtain zeaxanthin composite particles-1.

[0098] Formulation 2 (dry mixing and direct grinding): 10 g of zeaxanthin crystals, 10 g of modified starch, 3.2 g of mono- and diglycerol fatty acid esters (HLB value 3-6), 1.6 g of polyglycerol fatty acid esters (HLB 9-12), 3.2 g of sucrose fatty acid esters (HLB 15-18), 25 g of maltodextrin and 4 g of sodium ascorbate are directly mixed, mixed using a mixer, and then ground at -25°C for 15 min using a low-temperature freezing mill, then heated to 0°C and ground for 35 min, and finally heated to 30°C and ground for 10 min to obtain zeaxanthin composite particles-2.

[0099] Formulation 3 (low-temperature solid phase multiple co-grinding method): first, 10 g of zeaxanthin crystals were mixed with 3.2 g of mono- and diglycerol fatty acid esters (HLB value 3-6), and ground at -25°C for 15 min using a low-temperature freezing grinder to obtain co-grind 1; then, 10 g of modified starch, 1.6 g of polyglycerol fatty acid esters (HLB 9-12) and 3.2 g of sucrose fatty acid esters (HLB 15-18) were added and ground at 0°C for 35 min to obtain co-grind 2; finally, 25 g of maltodextrin and 4 g of sodium ascorbate were added and ground at 30°C for 10 min to obtain zeaxanthin composite particles-3.

[0100]

[0101] It can be seen from the above results that the contact angle of zeaxanthin crystals itself is greater than the contact angle of formulas 1, 2, and 3 after adding auxiliary materials, and it is a hydrophobic substance. Among them, formula 1 is a dry mix, and its contact angle is still >90°, and its solid surface is still hydrophobic. After the overall grinding of formula 2, the contact angle is <90°, and its solid surface is modified to hydrophilic. Formula 3, through the low-temperature solid phase multiple co-grinding method, through graded grinding, the contact angle of the material is gradually reduced, and finally a good hydrophilicity is achieved. In summary, the carotenoid composite microparticles prepared by the low-temperature solid phase multiple co-grinding method are the best.

[0102] Example 2 Effects of different preparation methods on carotenoid composite microparticles

[0103] Lutein composite microparticles A: Lutein composite microparticles were prepared by melting method. First, 30g of lutein crystals were dispersed and dissolved in 18g of vegetable oil to obtain the oil phase; then 20g of gum arabic, 6g of maltodextrin, 2g of polyglycerol fatty acid ester and 3g of sucrose fatty acid ester were fully dissolved in 60°C water; after the water phase was prepared, the oil phase was heated to 180°C, and after fully melting, it was slowly added to the water phase and quickly dispersed to form a coarse emulsion, 2g of sodium ascorbate was added, and finally, the emulsion was homogenized twice at a pressure of 50Mpa. The powder was dried in a spray drying tower (inlet air 190°C, outlet air 80°C), which was the lutein composite microparticles (A).

[0104] Lutein composite particles B: Lutein composite particles were prepared by wet grinding. 20g of gum arabic, 6g of maltodextrin, 2g of polyglycerol fatty acid ester and 3g of sucrose fatty acid ester were fully dissolved in water at 60°C; after cooling to 40-50°C, 30g of zeaxanthin and 2g of sodium ascorbate were added and stirred for more than 60 minutes for shearing to obtain a crude emulsion, and finally finely ground by a ball mill for 3 times to obtain an emulsion. The powder was dried in a spray drying tower (inlet air 190°C, outlet air 80°C), which was the lutein composite particles (B).

[0105] Lutein composite microparticles C: Lutein composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 30 g of lutein crystals were mixed with 2 g of polyglycerol fatty acid ester (HLB value 3-6), and ground at -10°C for 20 min using an ultrafine grinder to obtain co-grinding material 1; then 20 g of gum arabic, 1 g of sucrose fatty acid ester (HLB 9-12) and 2 g of sucrose fatty acid ester (HLB15-18) were added and ground at 0°C for 35 min to obtain co-grinding material 2; finally, 6 g of maltodextrin and 2 g of sodium ascorbate were added and ground at 30°C for 10 min to obtain lutein composite microparticles, namely lutein composite microparticles (C).

[0106] The contact angle, rehydrated particle size and stability of the above lutein composite particles A, B and C were monitored.

[0107] The particle size is measured by a laser particle size analyzer and the D90 value is recorded in μm.

[0108] The sterilization evaluation method is as follows: weigh the lutein composite particles at a concentration of 8 mg lutein composite particles / 100 ml, prepare a liquid solution, then adjust the pH to 3.5 with sodium citrate or sodium carbonate, place the solution in a sealed transparent glass vial, and heat it to 90°C. Determine the content of the lutein composite particles, determine the content retention rate during the sterilization process, expressed as a percentage; determine the color change after standing after sterilization; and observe the appearance change after sterilization.

[0109] Accelerated stability evaluation method: The Chinese Pharmacopoeia provides a method to determine the stability of carotenoid composite microparticles at different times under the conditions of 40°C and 75% RH. The carotenoid composite microparticle retention rate is used to indicate the stability of carotenoid composite microparticles. The carotenoid composite microparticle retention rate is the ratio of the carotenoid composite microparticle content at different times to the initial content, expressed as a percentage.

[0110]

[0111] The above results show that the contact angle of lutein composite microparticles C is the lowest, and its sterilization effect at 90°C is also the most uniform. At 40°C, 75% RH humidity, the accelerated degradation rate for 3 months shows that the HPLC content of lutein composite microparticles A prepared by the melting method is significantly lower than that of the other two products, which is the disadvantage of the melting method; while the lutein composite microparticles B and C prepared by the grinding method and low-temperature solid phase multiple co-grinding method have no significant reduction in content.

[0112] Example 3 Effects of different HLB values ​​and addition procedures in co-grinding on carotenoid composite particles

[0113] Formula 1: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 3), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 9) and 1.6 g of Tween (HLB value 15) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 1.

[0114] Formula 1-1: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 6), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 12) and 1.6 g of Tween (HLB value 18) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 1-1.

[0115] Formula 1-2: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 4), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 10) and 1.6 g of Tween (HLB value 16) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 1-2.

[0116] Formula 1-3: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 5), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then, 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 11) and 1.6 g of Tween (HLB value 17) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 1-3.

[0117] Formula 2: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 3), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 1.6 g of polyglycerol fatty acid ester (HLB value 9) and 1.6 g of Tween (HLB value 15) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 2.

[0118] Formula 2-1: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 6), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 1.6 g of polyglycerol fatty acid ester (HLB value 12) and 1.6 g of Tween (HLB value 18) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 2-1.

[0119] Formula 2-2: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 4), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 1.6 g of polyglycerol fatty acid ester (HLB value 10) and 1.6 g of Tween (HLB value 16) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 2-2.

[0120] Formula 2-3: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of mono- and distearic glycerol (HLB value 5), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 1.6 g of polyglycerol fatty acid ester (HLB value 11) and 1.6 g of Tween (HLB value 17) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 2-3.

[0121] Formula 3: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of Tween (HLB value 15), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then, 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB 3) and 1.6 g of mono- and distearic acid glyceryl ester (HLB 9) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 3.

[0122] Formula 3-1: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of Tween (HLB value 18), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 6) and 1.6 g of mono- and distearic acid glyceryl ester (HLB value 12) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 3-1.

[0123] Formula 3-2: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of Tween (HLB value 16), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 4) and 1.6 g of mono- and distearic acid glyceryl ester (HLB value 10) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 3-2.

[0124] Formula 3-3: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were mixed with 1.6 g of Tween (HLB value 17), and ground at 0°C for 20 min using a crushing impactor to obtain co-grind 1; then 30 g of modified starch, 0.8 g of polyglycerol fatty acid ester (HLB value 5) and 1.6 g of mono- and di-stearate glyceryl (HLB value 11) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 3-3.

[0125] Formula 4: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were ground at 0°C for 20 min using a crushing impactor to obtain grind 1; then 30 g of modified starch, 1.6 g of mono- and di-stearate glyceryl (HLB value 3), 0.8 g of polyglycerol fatty acid ester (HLB value 9) and 1.6 g of Tween (HLB value 15) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 4.

[0126] Formula 4-1: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were ground at 0°C for 20 min using a crushing impactor to obtain grind 1; then 30 g of modified starch, 1.6 g of mono- and di-stearate glyceryl (HLB value 6), 0.8 g of polyglycerol fatty acid ester (HLB value 12) and 1.6 g of Tween (HLB value 18) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain Formula 4-1.

[0127] Formula 4-2: Lutein ester composite particles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were ground at 0°C for 20 min using a crushing impactor to obtain grind 1; then 30 g of modified starch, 1.6 g of mono- and di-stearate glyceryl (HLB value 4), 0.8 g of polyglycerol fatty acid ester (HLB value 10) and 1.6 g of Tween (HLB value 16) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 4-2.

[0128] Formula 4-3: Lutein ester composite microparticles were prepared by using a low-temperature solid phase multiple co-grinding method. First, 20 g of lutein ester crystals were ground at 0°C for 20 min using a crushing impactor to obtain grind 1; then 30 g of modified starch, 1.6 g of mono- and di-stearate glyceryl (HLB value 5), 0.8 g of polyglycerol fatty acid ester (HLB value 11) and 1.6 g of Tween (HLB value 17) were added and ground at 40°C for 35 min to obtain co-grind 2; finally, 15 g of solid corn syrup and 1.0 g of ascorbic palmitate were added and ground at 20°C for 10 min to obtain formula 4-3.

[0129]

[0130]

[0131]

[0132] The above results show that the contact angle of formula 1 gradually decreases to 9°, while formula 2 only decreases to 19°, and formulas 3 and 4 show a significant gradual decrease. The corresponding formula 2 precipitates after sterilization at 120°C, while formulas 3 and 4 are obviously larger in particle size. Sterilization at high temperatures of 90 and 120°C also causes problems such as unevenness, stratification, and precipitation.

[0133] Example 4 Effect of different grinding temperatures on carotenoid composite particles

[0134] Formula 1: First, 22 g of β-carotene crystals and 3.0 g of diacetyl tartaric acid monoglyceride (HLB value 3-6) were mixed, and ground at -20°C for 20 min using a planetary mill to obtain co-grinding material 1; then, 40 g of cinnamyl succinate monoarabic gum ester, 1.5 g of Span (HLB 9-12) and 3.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 35 min to obtain co-grinding material 2; finally, 20 g of isomaltooligosaccharide, 0.5 g of mixed tocopherols, 0.01 g of ascorbic palmitate and 3 g of ascorbic acid were added and ground at 25°C for 10 min to obtain Formula 1.

[0135] Formula 2: First, 22 g of β-carotene crystals and 3.0 g of diacetyl tartaric acid monoglyceride (HLB value 3-6) were mixed, and ground at 20° C. for 20 min using a planetary mill to obtain co-grind 1; then, 40 g of arabic gum succinate, 1.5 g of Span (HLB 9-12) and 3.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20° C. for 35 min to obtain co-grind 2; finally, 20 g of isomaltooligosaccharide, 0.5 g of mixed tocopherols, 0.01 g of ascorbic palmitate and 3 g of ascorbic acid were added and ground at 25° C. for 10 min to obtain Formula 2.

[0136] Formula 3: First, 22 g of β-carotene crystals and 3.0 g of diacetyl tartaric acid monoglyceride (HLB value 3-6) were mixed, and ground at -20°C for 20 min using a planetary mill to obtain co-grind 1; then, 40 g of arabic gum succinate, 1.5 g of Span (HLB 9-12) and 3.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at -10°C for 35 min to obtain co-grind 2; finally, 20 g of isomaltooligosaccharide, 0.5 g of mixed tocopherols, 0.01 g of ascorbic palmitate and 3 g of ascorbic acid were added and ground at 25°C for 10 min to obtain Formula 3.

[0137] Formula 4: First, 22 g of β-carotene crystals and 3.0 g of diacetyl tartaric acid monoglyceride (HLB value 3-6) were mixed, and ground at -20°C for 20 min using a planetary mill to obtain co-grind 1; then, 40 g of arabic gum succinate, 1.5 g of Span (HLB 9-12) and 3.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 35 min to obtain co-grind 2; finally, 20 g of isomaltooligosaccharide, 0.5 g of mixed tocopherols, 0.01 g of ascorbic palmitate and 3 g of ascorbic acid were added and ground at 70°C for 10 min to obtain Formula 4.

[0138]

[0139] From the above results, it can be seen that temperature has a great influence on the system, which can be directly reflected in the rehydrated particle size.

[0140] Example 5 Effect of different grinding times on carotenoid composite particles

[0141] Formula 1: First, 15 g of lycopene crystals and 2.4 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground at 0° C. for 15 min using a crushing impactor to obtain co-grind 1; then, 25 g of octenyl succinic acid monoarabic gum ester, 1.2 g of polyglycerol fatty acid ester (HLB 9-12) and 2.4 g of sucrose fatty acid ester (HLB 15-18) were added, and the mixture was ground at 40° C. for 20 min to obtain co-grind 2; finally, 18 g of white granulated sugar, 1.0 g of ascorbic acid and 2.0 g of sodium ascorbate were added, and the mixture was ground at 20° C. for 20 min to obtain Formula 1.

[0142] Formula 2: First, 15 g of lycopene crystals and 2.4 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground with a pulverizer at 0° C. for 10 min to obtain co-grind 1; then, 25 g of octenyl succinic acid monoarabic gum ester, 1.2 g of polyglycerol fatty acid ester (HLB 9-12) and 2.4 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 40° C. for 20 min to obtain co-grind 2; finally, 18 g of white granulated sugar, 1.0 g of ascorbic acid and 2.0 g of sodium ascorbate were added and ground at 20° C. for 20 min to obtain Formula 2.

[0143] Formula 3: First, 15 g of lycopene crystals and 2.4 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground at 0° C. for 15 min using a crushing impactor to obtain co-grind 1; then, 25 g of octenyl succinic acid monoarabic gum ester, 1.2 g of polyglycerol fatty acid ester (HLB 9-12) and 2.4 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 40° C. for 10 min to obtain co-grind 2; finally, 18 g of white granulated sugar, 1.0 g of ascorbic acid and 2.3 g of sodium ascorbate were added and ground at 20° C. for 20 min to obtain Formula 3.

[0144] Formula 4: First, 15 g of lycopene crystals and 2.4 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground with a pulverizer at 0° C. for 15 min to obtain co-grind 1; then, 25 g of octenyl succinic acid monoarabic gum ester, 1.2 g of polyglycerol fatty acid ester (HLB 9-12) and 2.4 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 40° C. for 20 min to obtain co-grind 2; finally, 18 g of white granulated sugar, 1.0 g of ascorbic acid and 2.3 g of sodium ascorbate were added and ground at 20° C. for 25 min to obtain Formula 4.

[0145] Formula 5: First, 15 g of lycopene crystals and 2.4 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground with a pulverizer at 0° C. for 15 min to obtain co-grind 1; then, 25 g of octenyl succinic acid monoarabic gum ester, 1.2 g of polyglycerol fatty acid ester (HLB 9-12) and 2.4 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 40° C. for 50 min to obtain co-grind 2; finally, 18 g of white granulated sugar, 1.0 g of ascorbic acid and 2.3 g of sodium ascorbate were added and ground at 20° C. for 24 min to obtain Formula 5.

[0146]

[0147]

[0148] From the above results, it can be seen that different grinding times have a greater impact on the system, especially the impact on the grinding particle size, which directly affects the contact angle of its carotenoid composite particles.

[0149] Example 6 Effects of different amounts of carrier added on carotenoid composite particles

[0150] Formula 1: First, 12 g of fucoxanthin crystals and 4.0 g of mono- and distearic glyceryl (HLB value 3-6) were mixed, and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 10 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 1.

[0151] Formula 2: First, 12 g of fucoxanthin crystals were mixed with 4.0 g of mono- and distearic glyceryl (HLB value 3-6), and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 20 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 2.

[0152] Formula 3: First, 12 g of fucoxanthin crystals were mixed with 4.0 g of mono- and distearic glyceryl (HLB value 3-6), and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 30 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 3.

[0153] Formula 4: First, 12 g of fucoxanthin crystals were mixed with 4.0 g of mono- and distearic glyceryl (HLB value 3-6), and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 40 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 4.

[0154] Formula 5: First, 12 g of fucoxanthin crystals were mixed with 4.0 g of mono- and distearic glyceryl (HLB value 3-6), and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 5 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 5.

[0155] Formula 6: First, 12 g of fucoxanthin crystals were mixed with 4.0 g of mono- and distearic glyceryl (HLB value 3-6), and ground at -10°C for 20 min using a crushing impactor to obtain co-grind 1; then, 50 g of gum arabic, 2.0 g of polyglycerol fatty acid ester (HLB 9-12) and 4.0 g of sucrose fatty acid ester (HLB 15-18) were added and ground at 20°C for 20 min to obtain co-grind 2; finally, 12 g of oligomaltose, 0.5 g of ascorbyl palmitate and 3.0 g of sodium ascorbate were added and ground at 30°C for 20 min to obtain Formula 6.

[0156]

[0157] Different carrier addition amounts will have a direct impact on the contact angle and rehydrated particle size of carotenoid composite microparticles, thereby affecting their final effect.

[0158] Example 7 Evaluation test of application of Examples 1-6 in liquid beverages

[0159] (1) Beverage preparation method

[0160]

[0161] Preparation process: First, dissolve the carotenoid composite particles in Examples 1-6 in water and stir them thoroughly in a 50°C water bath, then add the fruit juice and mix thoroughly, then add sodium carboxymethyl cellulose, citric acid, erythritol, steviol glycoside and ascorbic acid in sequence and mix thoroughly, and take them out for use after mixing completely.

[0162] (2) Evaluation methods for beverage applications

[0163] A. Visually observe whether there is precipitation or floating oil

[0164] B. Sterilize at 90℃ for 30min and visually observe for precipitation and floating oil

[0165] C. Sterilize at 120℃ for 20min and visually observe whether there is precipitation or floating oil

[0166] Sedimentation 0-10 points, floating oil 0-10 points, the larger the score, the more serious the phenomenon

[0167] (3) Evaluation results

[0168]

[0169]

[0170]

[0171] According to the evaluation results of beverage applications, changing different process parameters and formula addition amounts will have different degrees of impact on its beverage application, especially when sterilized at high temperature, which will have a worse impact. It is necessary to control the process parameters and formula addition amounts within the required range.

[0172] Example 8 Evaluation test of the application of Examples 1-6 in tablets

[0173] (1) Tablet Manufacturing Method

[0174] 0.7 g of each of the carotenoid composite particles in Examples 1-6, 52.0 g of sorbitol, 46.62 g of microcrystalline cellulose, and 0.68 g of magnesium stearate were mixed to obtain a raw material powder. The raw material powder was used to make tablets with a diameter of 13 mm using a rotary tablet press (model: ZPW-8, Shanghai Tianfeng Pharmaceutical Equipment Co., Ltd.), each weighing 0.5 g and having a hardness of 100 N. The color of the carotenoid composite particles was observed by dispersing the colored carotenoid composite particles in the white tablets.

[0175] The prepared tablets were placed in a sealed HDPE bottle and stored in a constant temperature and humidity chamber set at 40°C / 75RH.

[0176] (2) Visual evaluation of the halo of carotenoid composite microparticle tablets

[0177] After preparation, the film was initially photographed and then randomly taken out after being stored at 40°C for 30 days and 60 days, and the halo of the carotenoid composite microparticles was observed under a microscope (50 times handheld microscope). The evaluation was marked with symbols according to the following criteria.

[0178] Ο: Good, basically no halo

[0179] Δ: Very slight dizziness

[0180] ◇: Generally a small amount of halo film

[0181] X: Severe dizziness

[0182] (3) Evaluation of the retention rate of carotenoid composite microparticles in tablets stored at 40°C for 30 days and 60 days (4) Evaluation results

[0183]

[0184]

[0185] According to the evaluation results, the carotenoid composite particles prepared within the specified range will not appear haloing phenomenon when stored at 40°C / 75RH for 30 days and 60 days in tablet applications, and the retention rate of the carotenoid composite particles is good, showing an excellent tableting effect. However, if it exceeds the scope of the invention requirements, there will be varying degrees of haloing phenomenon and poor retention rate of carotenoid composite particles.

[0186] Example 9

[0187] Granular composition structure definition:

[0188] Carotenoids, carriers, emulsifiers, small molecule fillers and antioxidants are present in the particles.

[0189] The carotenoids are present inside the particles as the objects to be protected and modified, and the emulsifiers are present between the carotenoids and the carriers as the medium, so that the groups in the carotenoids and the carriers are selectively arranged in a directional manner between the solids; the polar groups are facing the polar solid surface, the non-polar groups are pointing to the medium, the non-polar groups are facing the non-polar solid surface, and the polar groups are pointing to the medium; the bridging and bonding between surfaces of different polarities and incompatible surfaces are achieved. The small molecule filling fills the gaps on the surface of the carrier and mixes with the carrier. The antioxidants are distributed in the particles according to their different properties, wherein the fat-soluble antioxidants are present inside the particles together with the carotenoids, and the water-soluble antioxidants are present outside the particles together with the carriers and the small molecule filling.

[0190] Characterization of particle compositions (three different compositions are listed, with different contents, particle sizes, microstructures, contact angles and application directions; all can be prepared by patented processes and formulations.)

[0191]

[0192]

[0193] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A raw material composition of carotenoid composite particles, characterized in that: The carotenoid composition comprises at least one of lutein, zeaxanthin, fucoxanthin, lutein ester, β-carotene and lycopene; the total carotenoid content thereof is 5-20wt%; the carotenoid composition comprises the following components, calculated by weight: Carotenoid crystals: 5-30 parts by weight Carrier: 10-40 parts by weight Emulsifier: 0-8 parts by weight Small molecule filling: 6-25 parts by weight Antioxidant: 1-5 parts by weight.

2. The composition according to claim 1, characterized in that The carotenoid crystals have a total pigment content of 30-90wt% and a water content of less than 5%. The pretreatment method comprises: fully mixing marigold extract with 3-5 times the amount of anhydrous ethanol solution; adjusting the pH, performing isomerization stirring at 100-120°C, and then neutralizing, filtering, washing and drying to obtain the carotenoid crystals.

3. The composition according to claim 1, characterized in that The carrier is selected from at least one of modified starch, gum arabic, gum arabic octenylsuccinate, gelatin, agar, sodium caseinate and seaweed polysaccharide.

4. The composition according to claim 1, characterized in that The emulsifier is selected from at least one of sucrose fatty acid esters, polyglycerol fatty acid esters, mono- and di-glycerol fatty acid esters, diacetyl tartaric acid monoglyceride, phospholipids, Tween and succinate, and the HLB value is 3-18.

5. The composition according to claim 1, characterized in that The small molecule filler is selected from at least one of white sugar, glucose powder, maltooligosaccharide, solid corn syrup, isomaltooligosaccharide, fructooligosaccharide, resistant dextrin, lactose and xylitol.

6. The composition according to claim 1, characterized in that The antioxidant is selected from at least one of mixed tocopherols, dlα-tocopherol, ascorbyl palmitate, BHT, ascorbic acid, sodium ascorbate and tea polyphenols.

7. The composition according to claim 1, characterized in that The fat-soluble antioxidant is selected from at least one of mixed tocopherols, dlα-tocopherol, ascorbic palmitate and BHT.

8. The composition according to claim 1, characterized in that The water-soluble antioxidant is selected from at least one of sodium ascorbate, sodium ascorbate and tea polyphenols.

9. A carotenoid composite particle, characterized in that: The microparticles consist of carotenoids, carriers, emulsifiers, small molecule fillers and antioxidants, and have a contact angle of ≤20°.

10. The composite fine particles according to claim 9, characterized in that The particle size D90 of the microparticles is ≤1.5 microns.

11. The composite fine particles according to claim 9, characterized in that The moisture content of the microparticles is ≤4%; the ash content is ≤3%; the bulk density is between 0.40 and 0.70 g / mL; and the surface oil content is ≤0.5%.

12. The method for preparing carotenoid composite particles according to claim 9, characterized in that: The steps include: A) mixing the pretreated carotenoid crystals, emulsifier and antioxidant uniformly, and co-grinding at low temperature to obtain a co-grinding product 1; B) uniformly mixing the carrier, the emulsifier and the co-grinding material 1, and co-grinding again at low temperature to obtain a co-grinding material 2; C) The small molecule filler and the co-grinding material 2 are uniformly mixed, and after the third low-temperature co-grinding, the particles are sieved according to the required particle size to obtain carotenoid composite particles.

13. The method according to claim 12, characterized in that Step A) the co-grinding material 1 has a particle size of 10-600 μm and a contact angle of 60-90°; Step B) the co-grinding material 2 has a particle size of 10-600 μm and an antenna angle of 20-60°; Step C) The particle size of the co-grinding material 3 is 10-800 μm; the contact angle is 0-20°.

14. Use of the carotenoid composite particles according to claim 9 in food, health care products and cosmetics industries.

Citation Information

Patent Citations

  • Zeaxanthin pellets and preparation method thereof

    CN101703476A

  • Tablettable formulations of lipophilic health ingredients

    CN101873848B

  • Partition device

    CN101910526B

  • Pulverulent carotenoid preparation for colouring drinks

    CN105077203A

  • Lutein ester and water-soluble lutein ester microcapsule, and preparation methods thereof

    CN111718288A